Sb-Substituted Cs2AgBiBr6—As Much As It Could Be?—Influence of Synthesis Methods on Sb-Substitution Level in Cs2AgBiBr6 - Yoon, Songhak; Fett, Bastian; Frebel, Alexander; Kroisl, Sina; Herbig, Bettina; Widenmeyer, Marc; Balke, Benjamin; Sextl, Gerhard; Mandel, Karl; Weidenkaff, Anke (Energy Technology, 2022)
Sb-substituted Cs2AgBiBr6 single crystals and powders are synthesized by various wet-chemical routes as well as by solvent-free mechanochemical synthesis. Phase purity and resulting optical properties of differently synthesized Sb-substituted Cs2AgBiBr6 absorbers are investigated and compared. X-ray diffraction confirms that Sb substitution results in an apparent single-phase formation with a unit cell shrinkage up to a certain substitution limit, which varies depending on the synthesis routes. Questions about the phase identification determined by X-ray diffraction are raised and thoroughly investigated by Raman spectroscopy. UV–vis spectroscopy reveals that Sb3+ substitution induces a reduction in the optical bandgap of Cs2AgBiBr6, whereas octahedral factor calculations provide that SbBr6 octahedra can be hardly stable in a Cs2AgBiBr6 double perovskite. The experimental results of the occurrence and evolution of Raman bands and theoretical calculations of the structural stability of SbBr6 octahedra in Cs2AgBiBr6 unambiguously raise doubts about the Sb-substitution feasibility in Cs2AgBiBr6, and a general substitution strategy in Cs2AgBiBr6 is discussed.
CRIS-Team Scopus Importer:2022-08-19
Keywords: bandgap reduction; Cs; Pb-free photovoltaics; Raman spectroscopy; Sb substitution